Important differences in the diagnostic spectrum of primary immunodeficiency in adults versus children. (February 2014) - Abolhassani, Hassan; Rezaei, Nima; Mohammadinejad, Payam; Mirminachi, Babak; Hammarstrom, Lennart; Aghamohammadi, Asghar
<x xml:space="preserve">Abstract</x> Primary immunodeficiency disorders (PIDs) constitute a heterogeneous group of genetic disorders caused by defects in immunity, leading to recurrent infections, autoimmunity, lymphoproliferation and malignancies. Early diagnosis of PIDs is crucial for improving the quality of life in patients with PIDs while a delay in diagnosis, or inadequate treatment, results in an increased mortality and morbidity in affected individuals. Although most cases of PIDs present in children with recurrent and/or severe acute infections, some of the primary immune disorders are diagnosed during adulthood. Some common clues, both in children and adults, help physicians to diagnose PIDs; however, there are some specific clues to the diagnosis of PIDs for each group. This article reviews the important differences in the diagnostic spectrum of PIDs in adults versus children.